2013
DOI: 10.3174/ajnr.a3375
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative CT Densitometry for Predicting Intracerebral Hemorrhage Growth

Abstract: BACKGROUND AND PURPOSE:Intracerebral hemorrhage growth independently predicts disability and death. We hypothesized that noncontrast quantitative CT densitometry reflects active bleeding and improves predictive models of growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…In a recent study, Barras et al 19 developed a promising computer-assisted quantitative CT densitometry for assessment of hematoma heterogeneity. The technique is based on several derived parameters of CT densitometry that includes mean attenuation, square root of variance, coefficient of variation, skewness, and kurtosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Barras et al 19 developed a promising computer-assisted quantitative CT densitometry for assessment of hematoma heterogeneity. The technique is based on several derived parameters of CT densitometry that includes mean attenuation, square root of variance, coefficient of variation, skewness, and kurtosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanism of hematoma expansion is unclear, it may be attributable to persistent bleeding or re-bleeding from the initial blood vessel rupture or new foci of bleeding at the periphery of the lesion, often attributed to ischemia, poor venous flow, and local coagulopathy [80,81]. Large hematoma and a heterogeneous pattern can also be predictive of potential expansion [82,83]. The higher volume of hematoma expansion is associated with worse outcomes [79].…”
Section: Hematoma Expansionmentioning
confidence: 99%
“…Hematoma heterogeneity may partially reflect the presence of active extravasation within the hematoma in which uncoagulated blood appears iso-or hypodense relative to the brain parenchyma on CT [11]. Quantitative hematoma heterogeneity analysis using CT densitometry (CTD) is theoretically more robust, reproducible, and less prone to interpretation bias compared to qualitative techniques [5,6]. CTD may also facilitate rapid and reliable expansion prediction in the acute setting using semi-automated techniques [12].…”
Section: Introductionmentioning
confidence: 98%
“…Prevention of expansion is an attractive therapeutic target however improved means for expansion prediction are needed to guide potential acute interventions [3,4]. Previous studies have identified heterogeneity or low-attenuation within a hematoma on hyperacute NCCT, coined the 'swirl sign' , to be predictive of expansion and poor outcome [5][6][7][8][9][10][11]. Hematoma heterogeneity may partially reflect the presence of active extravasation within the hematoma in which uncoagulated blood appears iso-or hypodense relative to the brain parenchyma on CT [11].…”
Section: Introductionmentioning
confidence: 99%